Zn3(btc)2 as adsorbent for gas carbon dioxide and methane - Mohd Fathi, Muhammad (2009)
Adsorption is a process, which a substance in a gas or liquid becomes attached to a solid. This research is carried out in order to develop the storage from metal organic framework (MOFs) by adsorption application process. MOFs are crystalline compounds consisting of metal ions or clusters coordinated to often rigid organic molecules to form one-, two-, or three-dimensional structures that can be porous. MOFs are capable of storing large amount of gases. Zn3(btc)2 is one of MOFs and it promising storage materials. During this study, the adsorbent, Zn3(btc)2 has been developed and characterized as a storage for the carbon dioxide and methane The characteristic of Zn3(btc)2 as adsorbent was investigated with two parameter which is pressure and time. For the carbon dioxide, the pressures that were used are 2.0 bars, 4 bar and 6.0 bars and for the methane, the pressure that were used are 1.0 bar, 1.5 bars and 2.0 bars. Meanwhile, the parameter of time that used for both gases were same which are 1 hour, 2 hours, 3 hours and 4 hours. From this experiment, it was showed that, the weight of the sample after adsorption for both gases was increased. The experiment result showed that, methane gas was adsorbed more into Zn3(btc)2 compared to carbon dioxide gas This is because methane has smaller molecule size compare to carbon dioxide molecules which is 108.70 ppm and 116.3 ppm respectively. The rate of adsorption for both gases is low because the Zn3(btc)2 sample was not in crystallized form. This is as there are no proper autoclaves to synthesis the sample at 393 K and 12 hour. The characteristic of Zn3(btc)2 was investigated using Scanning Electron Microscope (SEM) in order to observe the structure of the Zn3(btc)2 before and after adsorption. From the observation, it was showed that the structure of Zn3(btc)2 was changed after the adsorption occurred. It is shown that the Zn3(btc)2 structure was expand and the amount of pore was decreased. From the result analysis, it was showed that the adsorption rate was affected more by pressure parameter compare to time parameter. As a conclusion, pressure and time of adsorption will affected the rate of adsorption however; the pore size of sample is still the most essential factor for an effective adsorption.-Author-